Living Conditions and Health in Indigenous Zones of Yucatan, Mexico: Changes Between 1990 and 2005 - Méndez González, Rosa María (2010)
Objective. Identify changes in living conditions and health in indigenous municipalities of Yucatan, Mexico, between 1990 and 2005. Methodology. The study was cross-sectional and comparative. Using two indicators: an index of social marginalization in which socioeconomic status was determined, and the infant mortality rate as an indirect indicator of health conditions. Statistical analysis was performed and a simple mapping analysis and relational. Results. From 1990 to 2005, worsened the living conditions and health in the municipalities of Yucatan. However, the deterioration was greater indigenous and the percentage of municipalities with high and very high degree of marginalization was higher in these municipalities (77% in 1990 and 92% in 2005) than nonindigenous (16% and 30 %). Also the proportion of municipalities that had rates of infant mortality with high and very high degrees was higher in indigenous municipalities (46% in 1990 and 48% in 2005) than non-indigenous (16% and 27% respectively). Between 1990 and 2005 increased the number of municipalities that had high degree of marginalization and also high degree of infant mortality (33% increased to 46%). There was a statistically significant association between infant mortality and deprivation index. Conclusions. Living conditions and health of indigenous peoples of Yucatan worsened from 1990 to 2005. The results suggest that it is urgent to reduce socioeconomic and health inequalities that prevailt in the Yucatan.